V23. Mutations in STX1B encoding a presynaptic protein cause fever-associated epilepsy syndromes. Issue 8 (August 2015) - Schubert, J.; Siekierska, A.; Esguerra, C.; Weber, Y.; Lerche, H.
<x xml:space="preserve">Abstract</x> Febrile seizures affect 2–4% of all children (Berg et al., 2013) and have a strong genetic component. (Eckhaus et al., 2013) Mutations in three main genes SCN1A, SCN1B, GABRG2 (Escayg et al., 2000; Wallace et al., 1998; Wallace et al., 2001) have been described to cause febrile seizures with or without epilepsy. In the present study, we identified mutations in the gene STX1B encoding syntaxin-1B (Südhof, 2013) which are associated with both febrile seizures and epilepsy. Syntaxin-1B plays an important role at the synapse as it is involved in the composition of the SNARE complex which mediates vesicle fusion at the membrane. The protein has two important domains. One is the so called Habc, which is located at the N-terminus. The second important domain is the SNARE domain at the C-terminus of the protein. Both domains are crucial for folding and binding in the SNARE complex in which, SNAP25 and synaptobrevin are also involved (Zhou et al., 2013). The identification of STX1B mutations was done by a combination of a linkage analysis and whole-exome/genome sequencing in two independent large pedigrees (Lerche et al., 2001; Weber et al., 2008). That approach revealed co-segregating STX1B mutations predicting an early truncation or an in-frame insertion/deletion which were located in the Habc and probably and most likely lead to an early truncation of the protein. Subsequently, we screened a cohort of 449 familial or sporadic cases and identified three additional nonsense or missense mutations in STX1B. One of the detected mutations even occurred de novo. These three mutations are located in the SNARE domain of the protein. Furthermore, a de novo microdeletion encompassing STX1B was identified by an array comparative genomic hybridization (CGH). To investigate the functional consequences at the protein level, we used an in vivo zebrafish model. To simulate the truncated state of the protein we established a stx1bknockdown. By field potential analyses of zebrafish larvae we were able to record seizure-like behavior and epileptiform discharges. Furthermore, we observed that increased temperature led to more frequent and longer discharges in the knockdown larvae. Beside the truncating mutations we also investigated one of the missense mutations. For this approach we chose the mutation which showed least genetic evidence. However, we also observed a decrease of epileptiform activity and discharges. We were further able to rescue the phenotype by wildtype syntaxin-1B. Our results thus implicate STX1B and the presynaptic release machinery in fever-associated epilepsy syndromes and give further evidence for epilepsy to be a "synaptopathy".